Criteria and guidelines for returning to running following a tibial bone stress injury: a scoping review - George, E. R. M.; Sheerin, K. R.; Reid, D. (Sports Medicine, 2024)
Tibial bone stress injuries (BSIs) are common among long-distance runners. They have a high recurrence rate, and complexity emerges in the wider management and successful return to running. Following a tibial BSI, a critical component of complete rehabilitation is the successful return to running, and there is a lack of consistency or strong evidence to guide this process. The objectives of this review were to outline the criteria used in clinical decision-making prior to resuming running, and to establish evidence-based guidelines for the return to running process following a tibial BSI. Electronic databases including MEDLINE, CINAHL, Scopus, SPORTDiscus and AMED were searched for studies that stated criteria or provided guidelines on the objectives above. Fifty studies met the inclusion criteria and were included. Thirty-nine were reviews or clinical commentaries, three were retrospective cohort studies, two were randomised controlled trials, two were pilot studies, one was a prospective observational study, and three were case studies. Therefore, the recommendations that have been surmised are based on level IV evidence. Decisions on when an athlete should return to running should be shared between clinicians, coaches and the athlete. There are five important components to address prior to introducing running, which are: the resolution of bony tenderness, pain-free walking, evidence of radiological healing in high-risk BSIs, strength, functional and loading tests, and the identification of contributing factors. Effective return to running planning should address the athlete`s risk profile and manage the risk by balancing the athlete`s interests and reinjury prevention. An individualised graduated return to running programme should be initiated, often starting with walk-run intervals, progressing running distance ahead of speed and intensity, with symptom provocation a key consideration. Contributing factors to the initial injury should be addressed throughout the return to run process.